2020
DOI: 10.15345/iojes.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the QR Code Game on Motivation in Suzuki Violin Lessons

Abstract: The aim of this study is to investigate the effect of QR code game in Suzuki violin lessons on student motivation. The design of the research is a qualitative case study. Suzuki violin first level pieces were examined with cognitive task analysis method and important technical tasks were revealed. The QR code game consists of two parts: White cards designed to predict pieces from technical tips. Yellowfun cards are designed to increase the repetition of the tracks and to provide greater motivation.These techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…When the studies conducted in the relevant literature are reviewed, it is seen that Çağla (2021) has research in which online piano education is examined in terms of student and teacher motivation, but this study is limited to piano education. In addition, it was observed that the research on online music/instrument training (Töral &Albuz, 2021;Çanakçı & Çoban, 2021;Afacan, 2022;Sakarya & Zahal, 2020;Kocamangil et al, 2021;Ertem & Akbulut, 2022;Sever, 2021;Kesendere et al, 2020;Aksoy & Nayir, 2020) were not subject to direct motivation, the studies on motivation in online education (Uçar, 2016;Bayındır, 2021;Bayraktar, 2015) were not directly related to music education and instrument training, and the studies on motivation in music education and instrument training (Özmenteş, 2013;Sungurtekin, 2010;Sever, 2020;Brody, 2020) did not provide information about online education. For this reason, it is aimed to conduct this research to eliminate the deficiency in the relevant literature.…”
Section: Introductionmentioning
confidence: 99%
“…When the studies conducted in the relevant literature are reviewed, it is seen that Çağla (2021) has research in which online piano education is examined in terms of student and teacher motivation, but this study is limited to piano education. In addition, it was observed that the research on online music/instrument training (Töral &Albuz, 2021;Çanakçı & Çoban, 2021;Afacan, 2022;Sakarya & Zahal, 2020;Kocamangil et al, 2021;Ertem & Akbulut, 2022;Sever, 2021;Kesendere et al, 2020;Aksoy & Nayir, 2020) were not subject to direct motivation, the studies on motivation in online education (Uçar, 2016;Bayındır, 2021;Bayraktar, 2015) were not directly related to music education and instrument training, and the studies on motivation in music education and instrument training (Özmenteş, 2013;Sungurtekin, 2010;Sever, 2020;Brody, 2020) did not provide information about online education. For this reason, it is aimed to conduct this research to eliminate the deficiency in the relevant literature.…”
Section: Introductionmentioning
confidence: 99%